Improved Quantum Ternary Arithmetics - Bocharov, Alex; Cui, Shawn X.; Roetteler, Martin; Svore, Krysta M. (2015)
Qutrit (or ternary) structures arise naturally in many quantum systems, particularly in certain non-abelian anyon systems. We present efficient circuits for ternary reversible and quantum arithmetics. Our main result is the derivation of circuits for two families of ternary quantum adders, namely ripple carry adders and carry look-ahead adders. The main difference to the binary case is the more complicated form of the ternary carry, which leads to higher resource counts for implementations over a universal ternary gate set.
arXiv preprint arXiv:1512.03824